Pengaruh budaya organisasi dan semangat kerja terhadap produktivitas kerja karyawan Bank BPR Rokan Hulu di kabupaten Rokan Hulu - Jeffi Gustriadi; Susi Hendriani; Errin Yani Wijaya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to determine how the variables influence organizational culture and Spirit of work simultaneously or partially on employee productivity BPR Bank Rokan Hulu in Rokan Hulu. The In this study, the population is BPR Bank employees Rokan Hulu in Rokan Hulu district, amounting to59 people.The sampling method used is census means all populations sampled in this study because the number of population is small . Analysis of the data used is descriptive analysis, but it is also a quantitative analysis that is using multiple linear regression with SPSS version 20.00. From the results of the testing that has been done , simultaneous regression test ( F-test ) showed that organizational culture and spirirt of work simultaneously significant effect on productivity. Partial Test Results (t test ) showed that the variables of organizational culture and \spirit of work partially significant effect on productivity. Based on the results of the analysis conducted should further enhance the organization's employees to the workings of employee productivity can be increased again. Organizations must also consider its employee culture within the organization so that employees have a sense of care for the job. And employee spirit of work should also be enhanced, so that employees are eager to finish the job .Keywords : Organizational Culture, Spirit of work and Productivity.